2014
DOI: 10.1016/j.ridd.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of socio-communicative skills in 9- to 12-month-old individuals with fragile X syndrome

Abstract: We investigated the early socio-communicative development of individuals with fragile X syndrome (FXS) by undertaking a retrospective analysis of family videos. Videos were analyzed to identify existing communicative forms and functions. Analyses were undertaken on seven children who were later diagnosed with FXS. The children were filmed when they were 9-12 months old and before being diagnosed. Fourteen different communicative forms and six different communicative functions were observed. All participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…An especially important aspect of this research involves collaborations between researchers and clinicians to help modify and implement effective intervention strategies to promote later language, social communication, and social interaction in individuals with FXS. The present study adds to the growing literature on identifying profiles of early social and communication behaviors in FXS (Flenthrope & Brady, 2010;Marschik et al, 2014;Roberts et al, 2002). To be specific, our findings highlight the need to more closely examine the developmental course of JE and early social behaviors in children with FXS, starting in infancy when these behaviors emerge.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…An especially important aspect of this research involves collaborations between researchers and clinicians to help modify and implement effective intervention strategies to promote later language, social communication, and social interaction in individuals with FXS. The present study adds to the growing literature on identifying profiles of early social and communication behaviors in FXS (Flenthrope & Brady, 2010;Marschik et al, 2014;Roberts et al, 2002). To be specific, our findings highlight the need to more closely examine the developmental course of JE and early social behaviors in children with FXS, starting in infancy when these behaviors emerge.…”
Section: Discussionmentioning
confidence: 62%
“…These studies on early communication development suggest that evidence for delays in language can be traced to deficits in early social communication behaviors. For example, deficits in early communicative gesture use have been reported (Flenthrope & Brady, 2010) as well as deficits in joint attention behaviors (e.g., commenting on an object by vocalizing, using gestures, and/or eye gaze shifts; Marschik et al, 2014;Roberts, Mirrett, Anderson, Burchinal, & Neebe, 2002). These deficits are likely to affect SJE and CJE because gestures, vocalizations, and joint attention are frequent means by which children demonstrate JE.…”
Section: Early Language Development In Fxsmentioning
confidence: 99%
“…In children and adults with FXS, social communication (i.e., pragmatics) is impaired, and these impairments are greater for individuals with comorbid ASD (Klusek, Martin, & Losh, 2014; Martin, Losh, Estigarribia, Sideris, & Roberts, 2013). However, the early social communication profile of infants and young children with FXS is largely unknown with few studies examining social communication at this age period (Flenthrope & Brady, 2010; Marschik et al, 2014; Roberts, Mirrett, Anderson, Burchinal, & Neebe, 2002). Marschik and colleagues (2014) investigated children with FXS 12 months and younger and found that most communication consisted of prelinguistic vocalizations with restricted gesture use.…”
Section: Introductionmentioning
confidence: 99%
“…However, the early social communication profile of infants and young children with FXS is largely unknown with few studies examining social communication at this age period (Flenthrope & Brady, 2010; Marschik et al, 2014; Roberts, Mirrett, Anderson, Burchinal, & Neebe, 2002). Marschik and colleagues (2014) investigated children with FXS 12 months and younger and found that most communication consisted of prelinguistic vocalizations with restricted gesture use. In slightly older children (21–77 months), deficits in reciprocity and gestures have also been reported (Roberts et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation